(untitled) (Biological Sciences - PJSIR, 1995)
A fast, accurate and comprehensive emission spectroscopic set-up has been employed to study the impactof copper vapour on an Ar-Cu mixture plasma. Temperature profiles in the arc have been determined in the absence ofCu vapour and then in its presence, using the absolute line intensity method for an Ar spectral line; these profiles have been compared with temperature profiles derived from relative intensities of Cu I lines. Temperature profiles derived from relative intensity ofCu I lines have been used to calculate the radial density distribution of copper atoms in the arc. The following observations have been made from the resulting atomic number densities: (i) the copper vapour concentrates in the fringes of the arc, with atomic number densities up to 8.6 X 1011 (cm’): and (ii) Cu atomic number densities in the core of the arc are small.